High Output Power and High Quantum Efficiency in Novel NIR Phosphor MgAlGa0.7 B0.3 O4 :Cr3+ with Profound FWHM Variation - Zhong, Chuansheng (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.